Business ideas that aspiring entrepreneurs are conceiving - De Vera, Ian Jester M. (Philippine Journal on Innovation and Entreperneurship, 2013)
This paper presents the data collected from the business plans submitted as part of the requirement of the Start Your Own Business Course run by the University of the Philippines Institute for Small-Scale Industries from 2006 to 2011. The Philippine Standard Industrial Classification provides the framework in assessing the type of products or services that the participants would develop into businesses. After analyzing the data gathered from the business plans submitted. to UP ISSI for the period covered, this paper formulates recommendations for the government and UP ISSI.